A secular agenda : for saving our country, for welding it - Shourie, Arun. (New Delhi : Harper Collins Publishers India, 1993)
With reference to India.
Includes bibliographical references and index.
Keywords: Secularism -- India. Religion and politics -- India. India -- Ethnic relations